Percutaneous endoscopic interlaminar decompression for degenerative scoliosis in the elderly: a safe and effective minimally invasive alternative - Zheng, Bin; Yu, Panfeng; Han, Tiepeng; Liu, Haiying; Liang, Yan (Frontiers in Surgery, 2025)
BackgroundElderly patients with degenerative scoliosis combined with spinal stenosis present significant treatment challenges. Traditional open fusion surgery carries high risks and complications in this population. This study investigates the clinical efficacy and safety of Percutaneous Endoscopic Interlaminar Decompression (PEID) as a potential minimally invasive alternative.MethodsA retrospective case series of 32 elderly patients (≥60 years) with degenerative lumbar scoliosis (Cobb angle 10°–30°) undergo PEID between January 2022 and December 2023. All procedures are performed under general anesthesia without internal fixation. Clinical outcomes are assessed using Visual Analog Scale (VAS) for pain and Oswestry Disability Index (ODI) for functional status. Radiographic evaluation includes measurement of scoliosis Cobb angles and adjacent intervertebral height. Follow-up is conducted at 1 week, 1 month, and 1 year postoperatively.ResultsThe study includes 14 males and 18 females with a mean age of 68.5 ± 6.1 years. The average operative time is 99.26 ± 13.17 min. VAS scores improved significantly from 7.4 ± 1.3 to 2.1 ± 0.7, and ODI from 55.0% ± 10.2% to 15.8% ± 5.0% at the final follow-up (both P < 0.01).According to modified Macnab criteria, 93% of patients achieve excellent or good outcomes. Minor complications occur in 2 patients (6.25%) with no major neurological complications. Radiographic analysis shows no significant progression of scoliosis (Cobb angle: 15.4° ± 6.2° vs. 15.7° ± 6.5°, P > 0.05) and no evidence of adjacent segment degeneration.ConclusionsPEID provides effective symptom relief and functional improvement for elderly patients with degenerative scoliosis, while maintaining spine stability. This minimally invasive approach offers a safe alternative to traditional open surgery in carefully selected patients with moderate scoliosis and primarily compressive symptoms.